Disaster Management System in Indonesia - Syugiarto, Syugiarto (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This study aims to determine the disaster management system in Indonesia and focuses on the outcomes and impacts given to the community. There are three steps used in looking at the disaster management system in Indonesia, including: 1). look at natural disasters (earthquakes and tsunamis) that occurred in Indonesia in a span of 20 years (2001 – 2021); 2). look at the disaster management system in Indonesia using 3 out of 4 disaster management cycles (mitigation, preparedness and response); 3). see the outcome and impact of disaster management regulations using a performance information framework. The method used in this research is library research. The results found in this study are that the disaster management system in Indonesia has not been running well in terms of outcomes and impact on the community. Within a span of 12 years (2009 – 2021) after the disaster management regulation was made, it has not been able to minimize the loss of life and financial losses experienced by the community. The inputs, processes and outputs of regulations and disaster management systems are in accordance with what has been conceptualized. But, the implementation process as well as the lack of disaster management regulations are the things that cause the outcomes and impacts cannot be realized and cannot protect the community from the threat of earthquakes and tsunamis.